Ionic co-crystals of enantiopure and racemic histidine with calcium halides. Issue 42 (28th September 2017) - Shemchuk, O.; Degli Esposti, L.; Grepioni, F.; Braga, D.
Abstract : Ionic co-crystals (ICCs) ofl - anddl -histidine with CaCl2, CaBr2 and CaI2 were prepared by mechanochemical and solution methods and were structurally characterized by either single crystal or powder X-ray diffraction methods. Abstract : Ionic co-crystals (ICCs) ofl - anddl -histidine with CaCl2, CaBr2 and CaI2 were prepared by mechanochemical and solution methods and were structurally characterized by either single crystal or powder X-ray diffraction methods. Thel -histidine molecules bridge Ca 2+ cations forming enantiopure ribbons in the homochiral crystals (l -His)2 ·CaX2 · n H2 O (X = Cl and Br n = 3, X = I n = 4), as well as in the partial dehydration product of (l -His)2 ·CaI2 ·4H2 O, namely (l -His)2 ·CaI2 ·3H2 O. In the racemic (dl -His)2 ·CaX2 ·4H2 O cases (X = Cl, Br, X = I), molecules of both chiralities are accommodated in the coordination sphere of the Ca 2+ cation forming ribbons with homochiral rims as in the enantiopure crystals. Intrinsic dissolution rate measurements show that the histidine-CaCl2 co-crystals have a much higher IDR with respect to both enantiopure and racemic histidine solids.